Adapting a substance use screening and brief intervention for peer-delivery and for youth in Kenya - Florence Jaguga; Mary A. Ott; Edith Kamaru Kwobah; Edith Apondi; Ali Giusto; Julius Barasa; Gilliane Kosgei; Wilter Rono; Mercy Korir; Eve S. Puffer (SSM - Mental Health, 2023)
Background: Substance use is a major problem among youth in sub-Saharan Africa, yet interventions that address this problem are scarce within the region. Screening and brief intervention is a cost-effective, efficacious, and easy to scale public health approach to addressing substance use problems. We conducted a pilot study to evaluate the feasibility of implementing a peer delivered screening and brief intervention program for youth in Kenya. The goal of this paper is to report on the process of adapting the Alcohol Smoking and Substance Involvement Screening Test for Youth-linked Brief Intervention (ASSIST-Y-linked BI) program for peer delivery and for the Kenyan context prior to the pilot. Methods: The adaptation process was led by a multi-disciplinary team comprised of psychiatrists, pediatricians, and psychologists. We utilized the ADAPT-ITT framework to adapt the ASSIST-Y-linked BI. The ADAPT-ITT framework consists of 8 phases including Assessment, Decision making, Adaptation, Production, Topical Experts, Integration, Training, and Testing the evidence-based intervention. Here, we report on phases 1–7 of the framework. The results of the pilot testing will be out in 2023. Results: Overall, we made surface level adaptations to the ASSIST-Y-linked BI program such as simplifying the language to enhance understandability. We maintained the core components of the program i.e., Feedback, Responsibility, Advice, Menu of Options, Empathy, Self-efficacy (FRAMES). Conclusions: Our paper provides information which other stakeholders planning to implement the ASSIST-Y-linked BI for youth in sub-Saharan Africa, could use to adapt the intervention.